REMAJA DAN MUSIK DANGDUT (Receiption Studies Musik Dangdut di Kalangan Remaja) - Nani Kurniasari (Universitas Bunda Mulia, 2014)
Dangdut in Indonesia is phenomenal entertainment. Authors observed how valuable dangdut that should be preserved as cultural existence, the enthusiasm for dangdut, popularity and its variations can reach a lot of people who hear it. However it is very far from the expectations of many people, especially from the observer music, music lovers, culturalist, intellectual circles, as well as the wider community. Obviously, they wanted an authentic dangdut, Indonesian character, manners in the work and performance on stage. Therefore, the author deems it necessary role of youth as young people in contributing good ideas, suggestions and constructive criticism for future glory dangdut. In the analysis required reception analysis, the meaning of which is negotiated by individual media based on their experience. Audiences implementing various social and cultural backgrounds obtained previously to read the text, so that the audience has different characteristics will interpret a text differently. Important for researchers to explore the meaning of teens that are based on things related to then bring up the 'messages' audience (teenagers) to dangdut has been packaged media. Keywords: dangdut, media, receiption studies, teenager